Three-Dimensional Uniaxially Aligned Nanofibre Construct Using Secondary Electrode Assisted Gap Electrospinning - Abdul Hamid, Nurfaizey; Salim, Mohd Azli; Tamaldin, Noreffendy; Razali, Nadlene; Kamarolzaman, Anita Akmar; Tucker, Nick (Universiti Malaysia Perlis, 2020)
Electrospinning is a simple, versatile, and scalable method of producing polymeric nanofibres from a solution or melt using electric charge. Due to their nanometre-scale diameters, electrospun fibres have been the subject of much study for applications that require a high surface area to volume ratio. However, challenges remain in spatially controlling the deposition of electrospun fibres due to the chaotic nature of electrospinning process. Due to the bending instability, electrospun fibres are typically deposited as random orientated fibres and furthermore, there is no control over the location where the fibres are deposited on the collector. Several techniques to control the deposition of electrospun fibres have been proposed; including the use of modified collectors and by reducing the tip-to-collector distances. Changes in solvent evaporation and the bending instability may reduce stretching of the fibre, resulting in larger diameter fibres. Recently, a new technique for controlling the deposition of electrospun fibres using charged secondary electrodes have been proposed and the results have been promising. In this study, a new approach of directly depositing uniaxially aligned nanofibres onto a holdable structure is demonstrated. The results suggest that the introduction of secondary electrodes charged with time-varying potentials could improve the alignment and distribution of fibres in the gap electrospinning process. The new technique would be able to produce fibres for applications which have been previously limited by physical constraint of conventional electrospun fibres.